Factors Related to Health Worker Performance: Systematic Review - Ainun Hafilda, Shafira; Misnaniarti, Misnaniarti; Syakurah, Rizma Adlia (Rifa'Institute, 2025)
Health human resources have a major impact in increasing the competitiveness of health services. The performance of health workers is a consequene of the needs and demands of society to obtain high quality health services. This research aims to determine the factors related to the performance of health workers. This type of research is a systematic review which is carried out by collecting and accumulating research related to factors related to the performance of health workers. The keywords used for literature searches;